Analysis of teachers Burnout syndrome in the Faculty of Engineering of the National University of Chimborazo and its Impact on Job Perfermance - Cabezas, Edmundo (2016)
The analysis of burnout in the teaching of engineering and its impact on job performance seeks to establish the cause why the lack of data on human behavior and academic training context occurs. The procedure used is that of operational variables in the case of burnout: emotional exhaustion, depersonalization, personal accomplishment and Workplace Performance: Personal, Family and Organizational through survey validated by experts and you set up a Burnout with test Maslach for burnout results rate: low, medium, high with ANOVAS and t multivariate for hypothesis testing to be the most affected dimension of personal and family size.